The relationship between productivity and tree-ring growth in boreal coniferous forests - Gea-Izquierdo, Guillermo; Bergeron, Yves; Huang, Jian-Guo; Lapointe-Garant, Marie-Pierre; Grace, John; Berninger, Frank (Finnish Environment Institute, 2016)
Peer reviewed